THE EFFECT OF COOPERATIVE LEARNING MODEL -TYPE NHT (NUMBERED HEAD TOGETHER) ON STUDENT LEARNING OUTCOMES OF CLASS X TKRO 2 OF SMK NEGERI 1 PALANGKA RAYA ON THE MATERIAL OF COMPONENT HYDRAULIC AND COMPRESSOR SYSTEM FOR ACADEMIC YEAR 2018/2019 - Fathur Rahman; Jhonni Rentas Duling (PARENTAS: Jurnal Mahasiswa Pendidikan Teknologi dan Kejuruan, 2020)
This research is carried out to investigate the effect of learning outcomes of students enter classes after applied NHT (Numbered Head Together) as type cooperative learning. The engineering subject such as component hydraulic system and compressors is planned being the class lesson for regarding study. This research implements True Experimental Design model based on the type of Posttest Control Design for 2 (two) groups. Each of them is selected randomly (R). The first group is given as treatment (x) while other does not be involved. The treated group is as the experimental group and subsequently the non-treated group is designed as the control group. After those implementations, the posttest denotes the experimental results in which the t-test with a significance level of ? = 0.05 has obtained a tcount of 8.99 while the ttable value was 2,000. Due to tcount > ttable, it can be concluded that there is an effect of using the NHT learning model (Numbered Head Together) on the student’s learning outcomes of class X TKRO 2 of SMK Negeri 1 Palangka Raya.